A study of risk factors for catheter associated urinary tract infection - P., Leelakrishna; Rao B., Karthik (International Journal of Advances in Medicine, 2018)
Background: Catheter associated urinary tract infections (CAUTIs) are the most common causes of UTIs in postoperative cases. Many risk factors are associated with its incidence. The present study was conducted with the aim to determine the related risk factors and to identify the causative agents contributing to the urinary tract infection. Methods: This prospective study was conducted on 210 patients meeting the requirements of inclusion criteria during September 2012 to February 2014. Detailed history of the patients was recorded. Urine culture was done at different time intervals to identify the causative agent suggestive to CAUTI. Univariate analyses of the association of each variable with CAUTI and multivariable logistic regression were done to predict CAUTI outcome. Results: The mean age of study participants was 51.61 years. Among them 141 were males and 69 were female patients. On univariate analysis purpose for urine catheterization, place of catheterization, breach in the closed system of drainage, duration of catheterization, hemoglobin value less than 10, raised renal parameters with serum creatinine more than 1.5 were all significantly associated with development of CAUTI (p value 0.000). Sex of the patient (p value 0.279) and catheter size (p value 0.279) was not found to have a significant correlation with increased risk of CAUTI. On multivariate analysis, age, catheter size, diabetes, duration of catheterization, a breach in the closed system of catheter drainage and sex were found to be the significant risk factors associated with CAUTI (p<0.05). Conclusion: An understanding of the risk factors in development of CAUTI, significantly helps in reducing the additional burden on the health care system. Measures such as shortening the duration of catheterization, strict control of diabetes and sterile precautions in insertion and maintenance of indwelling catheters can help in prevention CAUTI.